READING AND ANALYSIS OF A WORK OF FICTION AT THE UNIVERSITY (Web of Teachers: Inderscience Research, 2024)
This article discusses modern technical means and information technologies that play a key role in modern education. Technical means provide convenience and efficiency in the learning process. A variety of activities, such as working with key words, tasks of various kinds, illustrations and expressive reading, contribute to a deep understanding and comprehension of the work.